Heterogeneity of Microbial Communities in Soils From the Antarctic Peninsula Region - Almela, Pablo; Justel, Ana; Quesada, Antonio (Frontiers in Microbiology, 2021)
Ice-free areas represent less than 1% of the Antarctic surface. However, climate change models predict a significant increase in temperatures in the coming decades, triggering a relevant reduction of the ice-covered surface. Microorganisms, adapted to the extreme and fluctuating conditions, are the dominant biota. In this article we analyse the diversity and composition of soil bacterial communities in 52 soil samples in three scales: i) fine scale, where we compare the differences in the microbial community between top-stratum soils (0-2cm) and deeper-stratum soils (5-10 cm) at the same sampling point; ii) medium scale, in which we compare the composition of the microbial community of top-stratum soils from different sampling points within the same sampling location; and iii) coarse scale, where we compare communities between comparable ecosystems located hundreds of kilometres from each other along the Antarctic Peninsula. The results suggest that in ice-free soils exposed for longer periods of time (millennia) microbial communities are significantly different along the soil profiles. However, in recently (decades) deglaciated soils the communities are not different along the soil profile. Furthermore, the microbial communities found in soils of the different sampling locations have shown a high degree of heterogeneity, with a relevant proportion of unique amplicon sequence variants (ASV) that appeared mainly in low abundance, and only at a single sampling location. The Core90 community, defined as the ASVs shared by 90% of the soils from the 4 sampling locations, was composed of 26 ASVs, representing a small percentage of the total sequences. Nevertheless, the taxonomic composition of the Core80 (ASVs shared by 80% of sampling points per location) of the different sampling locations, was very similar, as they were mostly defined by 20 common taxa, representing up to 75.7% of the sequences of the Core80 communities, suggesting a greater homogeneity of soil bacterial taxa among distant locations.